Under the umbrella: components of empathy in psychology and design. (1st August 2022) - Chang-Arana, Álvaro M.; Surma-aho, Antti; Hölttä-Otto, Katja; Sams, Mikko
Abstract: Empathy is argued to be a key factor for a successful design discussion. However, such causality cannot be empirically proven based on how empathy is currently defined in design community. Empathy is used as an umbrella construct, broad and encompassing of diverse phenomena, making it difficult to quantify. We suggest improving such a situation by introducing a definition of empathy based on psychology literature, which provides structure and guidance for studying the role of empathy in design. We first break empathy to components. Then, we review empathy as used in design. Finally, we synthetize the reviewed material. From this synthesis, we conclude that empathy in design shares several key components of empathy in psychology; particularly with state influences, top-down control process and emotional stimuli. These are present in design methods although they have not been studied using such terms. Incorporating psychological components of empathy into design can help conceptualising empathy from a different angle, thus opening interesting new avenues for future research. We hope that our treatment provides present and future designers with some useful guidance.